Intraoperative radiotherapy (IORT) as a boost in patients with early-stage breast cancer: acute toxicity - Kraus-Tiefenbacher, Uta; Bauer, Lelia; Kehrer, Tanja; Hermann, Brigitte; Melchert, Frank; Wenz, Frederik (Onkologie, 2006)
Background: We report on acute toxicities as well as the early cosmetic outcome of patients receiving intraoperative radiotherapy ( IORT) followed by whole-breast radiotherapy ( WBRT) compared to patients treated with standard WBRT alone. Patients and Methods: From 2/2002 until 2/2005, 84 breast cancer patients were treated with IORT during breast-conserving surgery ( BCS) as a boost ( 20 Gy/50 kV X-rays) followed by WBRT. After wound healing, all IORT patients were treated with WBRT at a total dose of 46 Gy. For the purpose of comparison, 53 patients treated consecutively between 1/2003 and 12/2004 in our institution with BCS followed by WBRT at a total dose of 50-66 Gy, were analyzed. All patients had a defined follow-up schedule. Toxicities were prospectively documented using the CTC/EORTC Score. Cosmesis was evaluated after 6 months using a 1-4 score. Results: Treatment was well tolerated with no grade 3/4 acute toxicity. Rare adverse effects following IORT included wound healing problems ( 2%), erythema grade I-II ( 3%), palpable seroma ( 6%) and mastitis ( 2-4%). The number of patients with induration of the tumor bed was comparably low. Conclusion: IORT with the Intrabeam (TM) system applied as a boost during BCS, followed by 46 Gy WBRT, exerts similar acute toxicity as standard WBRT. Further follow-up is needed to assess long-term toxicity and efficacy.